PENGARUH DIGITAL MARKETING, ELECTRONIC WORD OF MOUTH, DAN FITUR MARKETPLACE TERHADAP KEPUTUSAN PEMBELI PADA TOKOPEDIA - Rizqy Nada Syavira (JURNAL BISNIS KOLEGA, 2024)
From the results of research conducted on Tokopedia users in Semarang, there are several problems that researchers can take into account, namely the influence of digital marketing, electronic word of mouth, and marketplace features on buyer decisions. This research aims to find out what factors can influence Tokopedia users in determining their purchasing decisions for goods or services available on the marketplace. The population in this study is unknown because there is no certainty about Tokopedia users in Semarang. Therefore, researchers used a purposive sampling technique with a total of 75 respondents. The data collection method was in the form of a questionnaire. Based on the research results, it can be concluded that partially, digital marketing variables have a positive and significant influence on buyer decisions. Meanwhile, from the results of the simultaneous test its is known that all variables have a significant influence on buyer decisions. Based on hypothesis testing, its is also known that the marketplace feature variable is the most dominant variable in buyer decisions.